2022
DOI: 10.1108/itp-04-2021-0329
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the affective affordances of videoconference technologies

Abstract: PurposeThe purpose of this study is to examine the role of videoconferencing technologies for mediating and transforming emotional experiences in virtual context.Design/methodology/approachDrawing on empirical data of video conferencing experiences, this study identifies different constitutive relations with technology through which actors cope with actual or potential anxieties in virtual meetings. It draws on the phenomenological-existential tradition (Sartre and Merleau-Ponty) and on an interpretive phenome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 66 publications
(163 reference statements)
2
8
0
Order By: Relevance
“…In particular, Twitter opened up and broadened out new socio-technical possibilities for developing resonant intra-connections between bodies echoing an understanding of atmospheric technologies (Beyes, Chun, Clarke, Flyverbom, & Holt, 2022). Its embodied affordances offered nuanced ways of sensual engaging, which gave rise to body-technology-other relations (Vidolov, 2022) constitutive of a communal body that was not merely premised on familiarity and proximity.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Twitter opened up and broadened out new socio-technical possibilities for developing resonant intra-connections between bodies echoing an understanding of atmospheric technologies (Beyes, Chun, Clarke, Flyverbom, & Holt, 2022). Its embodied affordances offered nuanced ways of sensual engaging, which gave rise to body-technology-other relations (Vidolov, 2022) constitutive of a communal body that was not merely premised on familiarity and proximity.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, during videoconferencing, users can see each other. This mutual gaze helps to co-construct emotional experiences among users [ 64 ]. Finally, the high level of naturalness in videoconferencing communication is similar to face-to-face talk, fulfilling the criteria of the media naturalness theory, which comprise:…”
Section: Discussionmentioning
confidence: 99%
“…As affordances were summarized based on the descriptions of participants, most of these were affective affordances, which could be roughly defined as the affordances related to human emotions. These affordances allow us to understand the emergence of emotions and their influence on the experience and engagement of participants (Vidolov, 2022) in the metaverse. Due to the affective nature of the participants' descriptions, we performed sentiment analysis to provide further support for our qualitative findings and identify the key factors contributing to user engagement.…”
Section: Methodsmentioning
confidence: 99%
“…Fuchs (2016) mentioned the notion of "affective affordance", suggesting that objects can also afford people emotions and affects. Using the concept of affective affordance, researchers understood the emergence of emotions (Vidolov, 2022) and their influence on user experience and engagement. Dincelli and Yayla (2022) reviewed 151 studies on immersive VR and identified five categories of affordances.…”
Section: Affordance Needs and Engagementmentioning
confidence: 99%